2010
DOI: 10.1021/nl903377u
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric Ribbons Printed onto Rubber for Flexible Energy Conversion

Abstract: The development of a method for integrating highly efficient energy conversion materials onto stretchable, biocompatible rubbers could yield breakthroughs in implantable or wearable energy harvesting systems. Being electromechanically coupled, piezoelectric crystals represent a particularly interesting subset of smart materials that function as sensors/actuators, bioMEMS devices, and energy converters. Yet, the crystallization of these materials generally requires high temperatures for maximally efficient perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
319
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(323 citation statements)
references
References 36 publications
3
319
0
1
Order By: Relevance
“…Recently, a series of rationally designed nanogenerators (NGs) with piezoelectric nanowires (NWs) have shown great potentialtoscavengetinyandirregularmechanicalenergy. [8][9][10][11][12][13][14][15] However, insufficient electric output hinders their practical applications. We report here a simple and effective approach, named scalable sweeping-printing-method, for fabricating flexible high-output nanogenerator (HONG).…”
mentioning
confidence: 99%
“…Recently, a series of rationally designed nanogenerators (NGs) with piezoelectric nanowires (NWs) have shown great potentialtoscavengetinyandirregularmechanicalenergy. [8][9][10][11][12][13][14][15] However, insufficient electric output hinders their practical applications. We report here a simple and effective approach, named scalable sweeping-printing-method, for fabricating flexible high-output nanogenerator (HONG).…”
mentioning
confidence: 99%
“…[ 2 , 3 ] State-of-the-art piezoelectrics are based on perovskite materials with complex chemistries including PbZr x Ti 1-x O 3 (PZT) at x = 0.52 and (1-x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PMN-PT) at x = 0.33. Special attention has been given to these materials due to the presence of morphotropic phase boundaries (MPB) -or a nearly temperature insensitive, compositionally driven boundary between tetragonal-and rhombohedral-polymorphs which gives rise to enhanced piezoelectricity.…”
mentioning
confidence: 99%
“…[4] Recently, it has been observed that MPB-like features can also exist in appropriately strained, chemically simple materials. [5,6,7] For instance, it has been shown that BiFeO 3 , which possesses a strong electrical polarization (~90-100 μC/cm 2 ) and is a candidate for the replacement of lead-based ferroelectrics, [8,9] can exhibit a strain-induced structural phase transition which gives rise to enhanced electromechanical response. [7] Using epitaxial thin film growth, X-ray reciprocal space mapping (RSM), atomic (AFM) and piezoresponse (PFM) force microscopy we report the nanoscale structural evolution of such strain-induced phase boundaries in BiFeO 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Of these transducers, piezoelectric materials have received the most attention because of their higher conversion efficiency. 6,7 Flutter is an aerodynamic phenomenon that occurs when a structure is subjected to flow loads, and this motion can be used to harvest wind energy in many applications using a piezoelectric cantilever. Erturk et al 8 have proposed a distributed parameter electromechanical model for a piezoelectric energy harvester and have carried out preliminary experiments with a flow induced airfoil.…”
Section: Introductionmentioning
confidence: 99%